2017
DOI: 10.1177/0300060517693422
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant sylvian vein: A newly described cause of pulsatile tinnitus

Abstract: We herein report a newly described cause of venous pulsatile tinnitus: protrusion of an aberrant sylvian vein into the tympanum. A 60-year-old woman presented with a 4-month history of objective persistent pulsatile tinnitus in the right ear with no other complaints. The pulsatile tinnitus diminished with rotation of the head to the right side or by compression of the right cervical vascular structures. The frequency and intensity of the tinnitus were 125 Hz and 20 dB HL, respectively. Audiometry and otoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…An unusual course of a SMCV over a dehiscent tegmen is an additional pressure element. This is supported by a previous report of a patient with venous pulsatile tinnitus due to a SMCV that coursed inferiorly to the temporal lobe and protruded into the tympanum through a dehiscent anterior cortical plate of the tympanum [28].…”
Section: Discussionsupporting
confidence: 84%
“…An unusual course of a SMCV over a dehiscent tegmen is an additional pressure element. This is supported by a previous report of a patient with venous pulsatile tinnitus due to a SMCV that coursed inferiorly to the temporal lobe and protruded into the tympanum through a dehiscent anterior cortical plate of the tympanum [28].…”
Section: Discussionsupporting
confidence: 84%
“…There was another reported case of pulsatile tinnitus due to protrusion of the SMCV into the tympanum. However, unlike our patient, that case had no scalloping of the mallear head (5).…”
Section: Discussioncontrasting
confidence: 77%
“…The DV in this study was also found to have obvious dehiscence toward air cells. This sign was also noted in patients with aberrant sylvian veins and petrosquamosal sinuses, which were identified as the causative findings of PT, respectively[ 11 , 12 ]. The mastoid emissary vein and posterior condylar vein have also been confirmed as the causes of PT, but descriptions of bone wall integrity are lacking[ 13 ].…”
Section: Discussionmentioning
confidence: 92%